On the Convergence of Iterative Receiver Algorithms Utilizing Hard Decisions. (11th January 2010) - Rößler Rößler, Jürgen F. Jürgen F.; Gerstacker Gerstacker, Wolfgang H. Wolfgang H.
Abstract : The convergence of receivers performing iterative hard decision interference cancellation (IHDIC) is analyzed in a general framework for ASK, PSK, and QAM constellations. We first give an overview of IHDIC algorithms known from the literature applied to linear modulation and DS-CDMA-based transmission systems and show the relation to Hopfield neural network theory. It is proven analytically that IHDIC with serial update scheme always converges to a stable state in the estimated values in course of iterations and that IHDIC with parallel update scheme converges to cycles of length 2. Additionally, we visualize the convergence behavior with the aid of convergence charts. Doing so, we give insight into possible errors occurring in IHDIC which turn out to be caused by locked error situations . The derived results can directly be applied to those iterative soft decision interference cancellation (ISDIC) receivers whose soft decision functions approach hard decision functions in course of the iterations.